Cascading off the West Greenland Shelf: A numerical perspective. Issue 7 (3rd July 2017) - Marson, Juliana M.; Myers, Paul G.; Hu, Xianmin; Petrie, Brian; Azetsu‐Scott, Kumiko; Lee, Craig M.
Abstract: Cascading of dense water from the shelf to deeper layers of the adjacent ocean basin has been observed in several locations around the world. The West Greenland Shelf (WGS), however, is a region where this process has never been documented. In this study, we use a numerical model with a 1/4° resolution to determine (i) if cascading could happen from the WGS; (ii) where and when it could take place; (iii) the forcings that induce or halt this process; and (iv) the path of the dense plume. Results show cascading happening off the WGS at Davis Strait. Dense waters form there due to brine rejection and slide down the slope during spring. Once the dense plume leaves the shelf, it gradually mixes with waters of similar density and moves northward into Baffin Bay. Our simulation showed events happening between 2003–2006 and during 2014; but no plume was observed in the simulation between 2007 and 2013. We suggest that the reason why cascading was halted in this period is related to: the increased freshwater transport from the Arctic Ocean through Fram Strait; the additional sea ice melting in the region; and the reduced presence of Irminger Water at Davis Strait during fall/early winter. Although observations at Davis Strait show that our simulation usually overestimates the seasonal range of temperature and salinity, they agree with the overall variability captured by the model. This suggests that cascades have the potential to develop on the WGS, albeit less dense than the ones estimated by the simulation. Key Points: Simulation shows cascading happening from eastern Davis Strait The dense water formed on the shelf goes to deep Baffin Bay The event may be halted due to an increase in freshwater content on the WGS